New pyrazolylpyrazoline derivatives as dual acting antimalarial-antileishamanial agents: synthesis, biological evaluation and molecular modelling simulations - Adnan A. Bekhit; Eskedar T. Lodebo; Ariaya Hymete; Hanan M. Ragab; Salma A. Bekhit; Kikuko Amagase; Afnan Batubara; Mohammed A. S. Abourehab; Alaa El-Din A. Bekhit; Tamer M. Ibrahim (Taylor & Francis Group, 2022)
Promising inhibitory activities of the parasite multiplication were obtained upon evaluation of in vivo antimalarial activities of new pyrazolylpyrazoline derivatives against Plasmodium berghei infected mice. Further evaluation of 5b and 6a against chloroquine-resistant strain (RKL9) of P. falciparum showed higher potency than chloroquine. In vitro antileishmanial activity testing against Leishmania aethiopica promastigote and amastigote forms indicated that 5b, 6a and 7b possessed promising activity compared to miltefosine and amphotericin B deoxycholate. Moreover, antileishmanial activity reversal of the active compounds via folic and folinic acids showed comparable results to the positive control trimethoprim, indicating an antifolate mechanism via targeting leishmanial DHFR and PTR1. The compounds were non-toxic at 125, 250 and 500 mg/kg. In addition, docking of the most active compound against putative malarial target Pf-DHFR-TS and leishmanial PTR1 rationalised the observed activities. Molecular dynamics simulations confirmed a stable and high potential binding of 7a against leishmanial PTR1.